Fluxograma do processo de planejamento arquitetônico aplicado a mercados públicos. - Oliveira Júnior, José Vanildo de (2006)
This work is a study of the evolutionary process of the Government-sponsored grocery markets and the revolution occurred at the grocery retail in the last decades. It identifies the architectural and urban parameters that are basis for a project methodology apply to Government-sponsored grocery markets. With this purpose, a research was done about the layout as well as the architectural shape of those markets throughout history; it was investigated the function and the new paradigms of retail, the importance of hygienic and secure food to define the parameters for quality control, the consumer decision-make process at the retail environment and the logic of the location for those urban equipment at the urban grid. At last, it is described the phases that compose the architectural planning of a Government-sponsored grocery markets, organizing a flowchart of activities to assure the development of a rational and systematic project process.